THE INFLUENCE OF WORK SPIRIT AND WORK LOYALTY ON EMPLOYEE PRODUCTIVITY - Data, Muhammad Umar (Association Of Indonesian Entrepreneurship Study Programs, 2024)
This research aims to examine and analyze the influence of work enthusiasm and work loyalty on employee work productivity at the Makassar City Trade Office. Data collection uses primary data obtained from questionnaires using primary data analysis techniques. The sample in this study was 35 Civil Servants who worked at the Makassar City Trade Office. The results of the questionnaire have been tested for Validity and Reliability, and also tested classic assumptions in the form of Normality Test, Autocorrelation Test, Multicollinearity Test, and Heteroscedasticity Test. The data analysis method uses descriptive statistical analysis techniques and inferential statistical analysis. Based on the results of the t test and the Multiple Linear Regression analysis carried out, it can be seen that the Work Morale Variable has a positive and insignificant effect on Employee Work Productivity at the Makassar City Trade Office. The Work Loyalty variable has a positive and significant effect on Work Productivity at the Makassar City Trade Office, and the Work Morale and Work Loyalty variables simultaneously have a positive and significant effect on Work Productivity at the Makassar City Trade Office